HOW DO MOMPRENEURS ACHIEVE WORK-LIFE BALANCE? (EVIDENCE FROM SMALL BUSINESS IN TANGERANG, INDONESIA) - Wijaya, Lindawati; Layman, Chrisanty Victoria (Journal of Business And Entrepreneurship, 2018)
Many housewives have started their own businesses, specifically in the micro sector in Indonesia, making them “mompreneurs.” A phenomenon observed from these mompreneurs is the struggle between their role as an entrepreneur and a housewife, which often creates conflict in the household. Interest arose in studies regarding problems and strategies carried out by mompreneurs to overcome such imbalance. Therefore, this study uses qualitative method, by looking into four mompreneur cases, to discover the realities of work-life balance of mompreneurs in Indonesia. The study uses NVIVO software to process and analyze information given from mompreneurs. Results of this study shows that the most problem faced by mompreneurs is family dependent care and time management. In addition, the strategy that is widely used by mompreneurs is delegation of tasks and building family relationships. The study seeks to contribute in raising awareness about mompreneurs’ life and their pursuit in achieving work-life balance. In addition, the results of the study further contributes in building the theories for mompreneurs business model in Indonesia.